MCMA acardiac twin: a trap? - S., Vinayachandran; Sudhakar, Vedhapriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Acardiac twining or Twin Reverse Arterial Perfusion (TRAP) is a rare complication of monozygotic twin occurring due to retrograde perfusion of acardiac twin by structurally normal pump twin through abnormal arterio-arterial anastomosis in the placenta. Here we report a case of unexpected occurrence of acardiac twin diagnosed as monozygotic monoamniotic twin (MCMA) gestation with single foetal demise due to multiple anomalies, delivered vaginally suggesting a role for expectant management.